Efektivitas Kinerja Keuangan Badan Amil Zakat Nasional (Baznas) pada Program Pentasharufan Dana Zakat di Baznas Kota Yogyakarta - Siti Nur Azizah (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2018)
This study discusses the effectiveness of the financial performance of Badan Amil Zakat (BAZNAS) in the distribution process of zakat funds (through zakat agents?), namely Jogja Taqwa, Jogja Peduli, Jogja Sehat, Jogja Cerdas, Jogja Sejahtera from 2012-2016. This research that was conducted in BAZNAS Yogyakarta, specifically analyzes the distribution of zakat funds using the Allocation to Collection Ratio (ACR) analysis method. It measures the ability of the zakat institution (BAZNAZ?) in distributing (the zakat fund?) (through zakat agents?) by dividing the total allocation funds to their total collection funds and comparing financial statements for several periods. The results of this study show the levels of effectiveness of zakat distribution of each year, year 2012 shows a